Functional properties of partially defatted peanut flour - Sarmiento, Carmina S. (College of Home Economics, University of the Philippines Diliman, 2019)
This study examined the functional properties of partially defatted peanut flour made from raw peanut fines. Minimum time to mechanically press raw peanut fines to expel majority of the oil was 120 minutes. After toasting, grinding and screening the peanut cake obtained from pressing, the resulting partially defatted peanut flour (PDPF) contained 36% protein, 39% fat, 1.6% moisture content and 0.3 water activity. The very low moisture and water activity content of the PDPF will help improve the keeping quality of the flour. However, considering that the fat content of the PDPF is high compared to commercially available partially defatted peanut flours (<28%), suitable packaging material should be used to minimize oxidation of fats, leading to longer storage times. Water and oil absorption capacity, emulsion stability, foam capacity and stability were significantly lower compared to the reference control, almond flour. Results obtained suggest that the PDPF alone has relatively high water and oil absorption capacities (152.26 ± 0.4 and 114.11 ± 1.49), good emulsion capacity (47.62 ± 0.00) and gelling capacity (6%). Based on these properties, PDPF can be used as an intermediate ingredient in soups, salad dressing, frozen desserts, and meats such as sausages and bologna. Aside from improving the nutritional and functional qualities of food, it can also help the environment since peanut fines or peanut meal wastes are utilized as a result of crushing or oil extraction processes.